Staggered wages, sticky prices, and labor market dynamics in matching models - Janett Neugebauer; Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2010)
This paper investigates the role of staggered wages and sticky prices in explaining stylized labor market facts. We build on a partial equilibrium search and matching model and expand the model to a general equilibrium model with sticky prices and/or staggered wages. We show that the core model creates too much volatility in response to a technology shock. The sticky price model outperforms the staggered wage model in terms of matching volatilities, while the combination of both rigidities matches the data reasonably well.
Keywords: E24; E32; J64; 330; Search and Matching; Staggered Wages; Sticky Prices; Arbeitsmarkttheorie; Lohnrigidität; Preisrigidität; Arbeitsuche; Arbeitsnachfrage; Matching; Allgemeines Gleichgewicht; Theorie